Bahasa Inggris - Tiara Istighfari; R. Myrna Nur Sakinah (ISTAJADDA : Jurnal Magister Pendidikan Agama Islam, 2025)
This study looks at the ideas of love and loss in the poems of Wallada bint al-Mustakfi (1001-1091). She was a well-known female poet from al-Andalus during the Taifa period in the Middle Ages. By closely reading her eight remaining poems, this study asks how her feelings relate to the big changes happening in 11th-century Islamic Iberia. The study especially looks at her rocky relationship with the famous poet Ibn Zaydun (1003-1071). Their relationship led to some of the most famous Arabic love poems and funny poems in medieval literature. The study shows that Wallada's poetry works in several connected ways. It shares her personal feelings of love and being betrayed. It also pushes back against the usual roles for women in literature. Plus, it comments on the unstable politics of her time. She boldly claimed power as a woman, like in her well-known verses sewn into fabric. They said she was worthy of "high positions" and could give her love as she pleased. This was a groundbreaking change from what people expected of women in medieval Islamic society. The research explains how she changed from a loving person to a critic using satire. This shows off her advanced writing skills, like how she twisted negative images of women and used metaphors skillfully.